2020
DOI: 10.1186/s13012-020-00988-y
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: a cluster randomized trial to evaluate the effectiveness and implementation of onsite GeneXpert testing at community health centers in Uganda (XPEL-TB)

Abstract: Background: Delays in diagnosis and treatment of tuberculosis (TB) remain common in high-burden countries. To improve case detection, substantial investments have been made to scale-up Xpert MTB/RIF (Xpert), a cartridgebased nucleic acid amplification test that can detect TB within 2 hours, as a replacement for sputum smear microscopy. However, the optimal strategy for implementation of Xpert testing remains unclear. Methods: The Xpert Performance Evaluation for Linkage to Tuberculosis Care (XPEL-TB) trial use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…If well-equipped laboratory infrastructure is scarce, automated cartridge-based PCR approaches provide an easy-to-implement solution for PCR in resource-poor tropical settings, as successfully proven by the rollout of GenXpert-(Sunnyvale, CA, USA-)based tuberculosis screening in sub-Saharan Africa [ 129 , 130 , 131 , 132 ]. Such assays are considerably easier to implement compared to traditional multiplex real-time PCR assays [ 133 ] and also available for gastroenteric pathogens [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…If well-equipped laboratory infrastructure is scarce, automated cartridge-based PCR approaches provide an easy-to-implement solution for PCR in resource-poor tropical settings, as successfully proven by the rollout of GenXpert-(Sunnyvale, CA, USA-)based tuberculosis screening in sub-Saharan Africa [ 129 , 130 , 131 , 132 ]. Such assays are considerably easier to implement compared to traditional multiplex real-time PCR assays [ 133 ] and also available for gastroenteric pathogens [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…XPEL-TB assessed whether providing decentralised point-of-care molecular testing using the GeneXpert Edge platform, in conjunction with streamlined clinical workflows and performance feedback via monthly report cards, would increase the number of people diagnosed with tuberculosis and reduce pre-treatment loss to follow-up, compared with routine care. 13 , 14 Ten health centres were randomised to receive this package, and had GeneXpert Edge systems installed onsite. The remaining ten centres were randomised to routine care, with SSM performed onsite and molecular Xpert testing performed at an off-site facility in accordance with national guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…10 , 11 , 12 However, this strategy's cost-effectiveness has not been well documented using empirical data, an important consideration for decision makers charged with allocating scarce resources. The Xpert Performance Evaluation for Linkage to Tuberculosis Care (XPEL-TB) trial in Uganda 13 showed that, relative to centralised testing, the XPEL-TB strategy—a multicomponent strategy focused around decentralised molecular testing—improved case detection and treatment initiation. 14 As part of the XPEL-TB study, we collected empirical economic data in the context of the trial to evaluate the cost and cost-effectiveness of the XPEL-TB strategy versus routine tuberculosis testing (onsite SSM plus centralised Xpert testing using a hub-and-spoke model).…”
Section: Introductionmentioning
confidence: 99%
“…The XPEL-TB Study was a cluster-randomized trial examining the effect of a multicomponent diagnostic strategy on the number of TB patients initiating treatment within 14 days of diagnosis. The intervention included on-site GeneXpert testing for TB and monthly feedback of quality metrics to staff [24][25][26].…”
Section: Study Design and Rationalementioning
confidence: 99%